Bishop-Runge approximations and inversion of a Riemann-Klein theorem. (28th February 2015) - Henkin, G M; Michel, V
Abstract In this paper we give results about projective embeddings of Riemann surfaces, smooth or nodal, which we apply to the inverse Dirichlet-to-Neumann problem and to the inversion of a Riemann-Klein theorem. To produce useful embeddings, we adapt a technique of Bishop in the open bordered case and use a Runge-type harmonic approximation theorem in the compact case. Bibliography: 37 titles.